Diabetic retinopathy - Wilmer Ophthalmological Institute. Retinal Vascular Center (Baltimore : The Center ; [St. Louis : for sale by Mosby], 1980)
(Critical) This is a clearly organized self-instructional module on diabetic retinopathy. Background information, preproliferative and proliferative retinopathy and management are discussed and indications, contraindications and complications of treatment, including photocoagulation and vitrectomy are covered. Diabetic maculopathy is mentioned, but too briefly considering its importance in visual loss. While this program is comprehensive, logical and consistant, the viewer needs a familiarity with diabetes and diabetic retinopathy for full comprehension; it is recommneded for resident ophthalmologic and continuing education.
Review date: Oct. 1980
Reviewer: Association of American Medical Colleges (AAMC)
Medical: undergraduate; graduate; continuing education. Specialty : ophthalmology
Keywords: Diabetic Retinopathy